Integrated fault diagnosis and control design of linear complex systems - Davoodi, Mohammad Reza; Meskin, Nader; Khorasani, K. 1960- (Institution of Engineering & Technology, 2018)
This book addresses the design challenges of developing and implementing novel integrated fault diagnosis and control technologies for complex linear systems.
Keywords: Control theory.; Fault location (Engineering); Linear systems.; Multiagent systems.; elektronické knihy; electronic books